Pengaruh Pemberian Tepung Bawang Dayak (Eleutherine Palmifolia Merr.) Terhadap Morfometrik Organ Dalam Dan Kadar Lemak Ayam Broiler The Effect Of Giving Dayak Union Flour (Eleutherine Palmifolia Merr.) On Organs Morphometric And Meat Fat Of Broiler Chicken - Lisnawaty Silitonga; Satrio Wibowo; Efrain Benediktus Bangun (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
This research was conduted to determine the effect of giving Dayak Onion flour in feed on organs morphometric and fat level of broiler chicken. This research used Completely randomized design (CRD) with four treatments and five replications. Each unit of experiment consisted of three broiler chickens. The treatments were P0 = feed without Dayak Onion flour, P1 = feed + 5 % Dayak Onion flour, P2 = feed + 10 % Dayak Onion flour and P3 = feed + 15 % Dayak Onion flours. This research was conducted in the experimental cage of livestock study program in May to June 2019. The autcomes showed that the requrement of Dayak Onion flour with a higher level to the lower final weight of broiler chickens, but the administration of Dayak Onion flour at the 5% level in the ration could increase the weight of broiler chicken carcasses. Dayak Onion flour with a higher level causes a higher percentage of the weight of proventriculus, gizzard and liver, but the small intestine gets shorter as the level of Dayak Onion is given in the ration. Giving Dayak Onion flour with a higher level of  giving in the ration can reduce the fat contents of broiler chicken meat.